Adjoint curves of special Smarandache curves with respect to Bishop frame - Esra Damar (AIMS Mathematics)
In this paper, adjoint curves generated by means of integral curves of special Smarandache curves with respect to the Bishop frame in three-dimensional Euclidean space were introduced. Relations between the main curve and the Bishop apparatus of these adjoint curves were obtained. Some important results were given concerning the slant helix and general helix of these curves. Finally, these findings were illustrated with figures.